Structure of pulse processing in India - Roy, Devesh; Chandra, Raj (International Food Policy Research Institute, 2017)
In this chapter, we analyze the pulse processing sector’s growth and the relative roles of the organized and the unorganized sectors of the industry. We also identify the constraints facing pulse processing and suggest a way forward for the sector.